Natural Habitat, Housing, and Restraint of Six Selected Neotropical Animals in Trinidad and Tobago with the Potential for Domestication - Kavita Ranjeeta Lall; Kegan Romelle Jones; Gary Wayne Garcia (Scientifica)
This paper highlights the natural habitat, housing, and restraint needs of 6 Neotropical animals that are found in Trinidad and Tobago with the potential for domestication: agouti (Dasyprocta leporina), lappe/paca (Cuniculus paca/Agouti paca), capybara (Hydrochoerus hydrochaeris), manicou/opossum (Didelphis marsupialis insularis), collared peccary (Tayassu tajacu/Pecari tajacu), and red brocket deer (Mazama americana). The year of the earliest reference cited was 1950 and the most recent was 2018, with over 100 references being used. The average density, home range size, social group, and housing requirements were also examined as these factors would play a role in designing enclosures. A number of different physical and chemical restraint techniques were also discussed. Information from other species within the same genus was incorporated as some of the animals did not have sufficient literature.